"They Will Come to Understand": Supervisor Reflections on International Medical Electives. Issue 4 (2nd October 2018) - Roebbelen, Erica; Dorman, Katie; Hunter, Andrea; Kraeker, Christian; O'Shea, Tim; Bozinoff, Nikki
ABSTRACT: Phenomenon : Increasing numbers of medical students from high-income countries are undertaking international medical electives (IMEs) during their training. Much has been written about the benefits of these experiences for the student, and concerns have been raised regarding the burden of IMEs on host communities. The voices of physicians from low- and middle-income countries who supervise IMEs have not been explored in depth. The current study sought to investigate host–physician perspectives on IMEs.Approach : Host supervisors were recruited by convenience sampling through students travelling abroad for IMEs during the summer of 2012. From 2012 through 2014, 11 semistructured interviews were conducted by telephone with host supervisors from Nepal, Uganda, Ghana, Guyana, and Kenya. Participants were invited to describe their motivations for hosting IMEs and their experiences of the benefits and harms of IMEs. Interviews were transcribed verbatim and checked for accuracy. An initial coding framework was developed and underwent multiple revisions, after which analytic categories were derived using conventional qualitative content analysis.Findings : For host supervisors, visits from international medical students provided a window into the resource-rich medical practice of high-income countries, and supervisors positioned themselves, their education, and clinical expertise against perceived standards of the international students' context. Hosting IMEs also contributed to supervisors' identities as educators connected to a global community. Supervisors described the challenge of helping students navigate their distress when confronting global health inequity. Finally, the desire for increasingly reciprocal relationships was expressed as a hope for the future.Insights : IMEs can be formative for host supervisors' identities and are used to benchmark host institutions compared with international medical standards. Reciprocity was articulated as essential for IMEs moving forward.